2020
DOI: 10.1177/2333794x20975628
|View full text |Cite
|
Sign up to set email alerts
|

Expectant Fathers’ Social Determinants of Health in Early Pregnancy

Abstract: This cross-sectional, descriptive study examined unmet social and economic needs and health information requests of low-income, expecting fathers who participated in the First 1000 Days program. The First 1000 Days is a systems-level intervention aiming to prevent obesity among low-income mothers and infants across 3 community health centers in Greater Boston, MA, USA. Fathers who attended their partner’s first prenatal care visit were invited to complete a program survey during early pregnancy. Among 131 fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…There are a number of articles that describe what pregnant women and professionals in maternal and child health identify as the roles of fathers (Alio et al, 2013; Eggermont et al, 2017; Neri Mini et al, 2020; Xue et al, 2018). In our study, we found that fathers fully grasped the breadth and gravity of their new roles and responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of articles that describe what pregnant women and professionals in maternal and child health identify as the roles of fathers (Alio et al, 2013; Eggermont et al, 2017; Neri Mini et al, 2020; Xue et al, 2018). In our study, we found that fathers fully grasped the breadth and gravity of their new roles and responsibilities.…”
Section: Discussionmentioning
confidence: 99%